Success Factors: An Empirical Investigation of MSME Entrepreneurs: Exploring the Factors Influencing Success of MSME Entrepreneurs in the Indian Industrial Sector (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The objective of this study is to analyse various factors required for the success of an enterprise In the industrial sector of India the contribution of MSME sector has been very significant. It contributes about 45 in manufacturing and 40 of the total export of the country. Thus the objective of the study is to examine the success factors of entrepreneurs in this sector. The data were collected from 120 entrepreneurs using a questionnaire. The data have been analysed descriptively and presented through figures, tables and percentages. Moreover, factors analysis was also conducted to group these factors in to various groups. The results suggest that finance management, availability of customers and family support affect positively and significantly to the success of entrepreneurs in their business.